The march to sustainability of agriculture through contract farming - how will the youth fare? - Alby, Jeffrey Lawrence D'Silva; Abu Samah, Bahaman; Mohamed Shaffril, Hayrol Azril (Ontario International Development Agency, 2012)
Undoubtedly modern farming methods are important as the driver that will enable the sustainability of agriculture and one of it is contract farming that is believed to have a high prospect in enabling the agriculture sector to accomplish the mission of sustainability. It is often said that one of the pertinent groups in any society is the youth and their contribution is indeed vital in safeguarding the agriculture sector and its’ march to sustainability. Thus, the aim of this study is to investigate the level of acceptance of youth toward contract farming and its’ contributing factors. The data for this study was collected via a survey method and a total of 400 students from four tertiary institutions in Malaysia participated in this study. The outcome of the study depicted that the respondents had a highly positive acceptance toward contract farming and its’ significant predictors were attitude, knowledge and belief. It was further identified that education plays an important role in motivating our youth to be involved in agriculture. Moreover, the study too showed that with proper exposure of knowledge and information, youth are determined to accept and be involved in agriculture in an enterprising manner.